2010
DOI: 10.1158/0008-5472.can-10-1534
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Mediates DNA Demethylation Events Triggered by Retinoic Acid during Neuroblastoma Cell Differentiation

Abstract: Neuroblastoma is an often fatal pediatric cancer arising from precursor cells of the sympathetic nervous system. 13-Cis retinoic acid is included in the treatment regimen for patients with high-risk disease, and a similar derivative, all-trans-retinoic acid (ATRA), causes neuroblastoma cell lines to undergo differentiation. The molecular signaling pathways involved with ATRA-induced differentiation are complex, and the role that DNA methylation changes might play are unknown. The purpose of this study was to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 27 publications
0
85
1
1
Order By: Relevance
“…miRNA profiles can predict survival of patients with neuroblastoma, therefore, making targeting miRNAs with antagomirs (oligonucleotides that block miRNA activity) a promising therapy [221]. In addition to altering miRNA expression, RA can induce genome-wide changes in DNA methylation by increasing expression of DNA methyltransferases and concomitant hypomethylation of promoters during neuroblastoma differentiation [222]. These changes in miRNA and DNA methylation alter the epigenetic landscape and ultimately affect the expression of oncogenes and tumorsuppressor genes.…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…miRNA profiles can predict survival of patients with neuroblastoma, therefore, making targeting miRNAs with antagomirs (oligonucleotides that block miRNA activity) a promising therapy [221]. In addition to altering miRNA expression, RA can induce genome-wide changes in DNA methylation by increasing expression of DNA methyltransferases and concomitant hypomethylation of promoters during neuroblastoma differentiation [222]. These changes in miRNA and DNA methylation alter the epigenetic landscape and ultimately affect the expression of oncogenes and tumorsuppressor genes.…”
Section: Downstream Effectors Of Retinoic Acid Signaling Related To Nmentioning
confidence: 99%
“…All but 7 miRNAs were changed in the same direction when high-N-myc and low-N-myc states were compared in both species. Principal component analysis (PCA) suggested that N-myc regulates similar miRNAs in human and mice, including miRNAs with established functions in neuroblastoma, like members of the mir-17-92 cluster (54, 63), mir-9 (57), and mir-152 (78). The miRNA profiles across murine tumors were more homogeneous than in human tumors, which might reflect the inbred genetic environment in mouse versus human tumors (77).…”
Section: Mycn-driven Mirna Expression In a Murine Transgenic Neuroblamentioning
confidence: 99%
“…Overexpression of mir-101 and let-7e in MYCNamplified neuroblastoma cells diminished N-myc levels, and reduced proliferation and clonogenic growth. While mir-101 is generally sparsely expressed in neuroblastoma and has established tumor-suppressor functions in other cancers [(100) and references therein], let-7 family members are upregulated during neuroblastoma cell differentiation (47,56,78,(101)(102)(103), suggesting tumor suppressor functions for these miRNAs in neuroblastoma.…”
Section: N-myc Expression Is Regulated By Mirnasmentioning
confidence: 99%
“…Overexpression of miR-152 in SK-N-BE cells mimicked some, but not all, of the features of differentiation seen with retinoic acid treatment, suggesting that miR-152 is only partially responsible for phenotype in this system (118) .…”
Section: Retinoic Acidmentioning
confidence: 93%
“…Vitamin D supplementation is now being investigated in the treatment and prevention of these diseases, with a particular focus on its potential as a cancer chemopreventative, due to the identified role of the vitamin D receptor (VDR) in cell-cycle regulation and differentiation (86) . The active vitamin D metabolite, calcitriol (1,25-dihydroxyvitamin D 3 ), has long been known to directly (50) Choline deficiency (114) , methyl group deficiency (112) 126 (49) Vitamin C deficiency (131) 152 (118) Retinoic acid treatment (118) DNMT3 29 (47,48) Folate/methyl group deficiency (108) , retinoic acid treatment (123) 222 (95) Vitamin D treatment (90) Histone methyltransferase SUV39H1 125b (57) Vitamin E deficiency (142) , retinoic acid treatment (117,120) , vitamin D treatment (89) HDAC and HAT 206 (64) Retinoic acid treatment (117,120) 22 (94) Vitamin D treatment (92) HDAC 627 (96) Vitamin D treatment (96) DNMT, DNA-methyl transferase; HDAC, histone deacetylase; HAT, histone acetyltransferase.…”
Section: Vitamin Dmentioning
confidence: 99%